Seventh Five Year Plan 1985-1990 State of West Bengal Mid-Term Appraisal - Planning Commission (Planning Commission, 1987)
A new approach to production planning has been attempted in West Bengal in the recent years. Within the limitation of the existing socio-economic structure, the alternative approach begins, by trying to reorder, to whatever extent possible, the existing distribution of production assets, in agriculture and industry, towards a more equitable situation. This approach therefore begins in agriculture with redistributive land reforms, and in industry with duo emphasis on small-scale units with the necessary support of certain crucial “mother” industrial complexes.
Government of West Bengal, Development and Planning Department